Effects of Minimal Extracorporeal Circulation on the Systemic Inflammatory Response and the Need for Transfusion after Coronary Bypass Grafting Surgery. (4th June 2019) - Elçi, Mehmet Emre; Kahraman, Aydın; Mutlu, Emre; İspir, Cemil Selim
Abstract : Objectives . The aim of this study is to compare the effects of the minimal extracorporeal circulation (MiECT) on postoperative systemic inflammatory response and the need for transfusion in patients undergoing open heart surgery with cardiopulmonary bypass. Methods . Patients were divided into two groups; Group M (n = 31 ) included the patients operated via using the MiECT system and Group C (n = 27 ) included the patients operated via using conventional cardiopulmonary bypass (CPB). Perioperative markers of inflammation after cardiopulmonary bypass in both groups were tested by measuring the levels via chemiluminescent immunometric assay. Blood samples were taken consecutively after anesthesia induction, 30 th minute of CPB, on the 6 th, 24 th, and 48 th hours after cardiopulmonary bypass. Results . The mean amount of priming solution was significantly lower in Group M when compared to Group C (802.60 ± 48.26 and 1603.71 ± 49.85 ml). The mean hematocrit (Hct) value taken immediately after cardiopulmonary bypass was found to be significantly higher in the MiECT patients with respect to the other group (% 32.71 ± 3.98 and % 28.82 ± 4.39). The transfused amounts of erythrocyte suspension and fresh frozen plasma were found to be significantly lower in patients in Group M when compared to those in Group C. Postoperative mediastinal drainage was also significantly lower in patients in Group M with respect to the other group. There was no significant difference between markers of inflammation. Conclusion . Our results show that MiECT seems to be more advantageous in terms of priming volume, perioperative hematocrit levels, need for blood and blood product transfusion, and mediastinal drainage with respect to the conventional approach after coronary artery bypass grafting.